DIELECTRIC PROPERTIES OF Mg:Al LAYERED DOUBLE HYDROXIDES - Giraldo Osorio, Óscar Hernán (2015)
This work describes the synthesis and characterization of Mg2Al-NO3 layered doublehydroxides nanomaterial prepared using a coprecipitation method. The electrical behavior ofthis material was evaluated using dielectric spectroscopy. The results from X-ray diffractionanalysis showed the formation of lamellar structure, while the atomic absorption and infraredspectroscopy confirms the presence of all species inthe structure of the synthesized material.TEM shows clusters of plate-like particles and the dielectric spectroscopy results at roomtemperature show an orientational polarization behavior that suggests the rotation of watermolecules at high frequency. TEM results also demonstrate the rotation of nitrate anions inthe interlayer spacing at low frequency, which may be responsible for producing anionicconductivity.